Optimization of Indonesia-Singapore Border Security Operations to Enhance Maritime Security in the Singapore Strait - Prasetyaji, Hana; Sumantri, Rudi; Yulianto, Erwin Tri (Journal of Industrial Engineering & Management Research, 2024)
The Singapore Strait is an Indonesia-Singapore sea border area with strategic significance and high economic value. It is one of the world's most densely populated shipping lanes, with more than 70,000 ships passing through each year. The high economic value of the Singapore Strait is directly proportional to the increase in transnational crimes in these waters. Some incidents of lawlessness that occur in the Singapore Strait include piracy, drug trafficking, human trafficking, illegal immigrants, people smuggling, firearms smuggling, electronic goods smuggling, used clothing smuggling and other goods smuggling activities. Indonesia and Singapore have conducted dialogue and negotiations to resolve maritime boundary issues, mainly related to the territorial sea boundary in the eastern segment of the Singapore Strait, to which neither country has fully agreed. This issue poses various maritime security challenges in these waters. Considering the potential and naval threats in the Singapore Strait, the Indonesian Navy has made these waters one of the hot spot areas prioritised for Border Security Operations. The Indonesian Navy has conducted routine Operation Pamtas using KRI elements, which aims to provide a sense of security to all sea users in the Singapore Strait from the threat of violence, the threat of law violations, the threat of theft of marine resources and navigation threats.